PENGARUH PENERAPAN METODE DISKUSI FISH BOWL TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 SOLOK SELATAN TAHUN PELAJARAN 2013/2014 - Sari, Diah Ratna; Aima, Zulfitri; Cesaria, Anna (STKIP PGRI Sumbar, 2013)
The background of this research told about studentâs concept comprehension that lower so the result of studentâs mathematics learning much of them canât achieve the minimum passing grade yet and students cannot find creative ideas in learning process . The purpose of this research to determine what is mathematics concept comprehension students by applying the method of discussion (Fish Bowl) better than studentâs learning conventional at VIII grade SMPN 3 Solok Selatan 2013/2014. The population was students VIII grade SMPN 3 Solok Selatan 2013/2014 consist of two classes. The sample of this research is VIIIb as experiment class and VIII b as class control. Instrument using test comprehension concept studentâs mathematics have essay test with reliability test 0.83. Hypothesis test using MINITAB t-test. The result of the data analysis P-value 0,033 less from Î± that 0, 05 so the hypothesis was accepted, in concluded that studentâs mathematics concept with applying discussion method (Fish Bowl) better than learning conventional at VIII grade at SMPN 3 Solok Selatan 2013/2014 Â Â